2015
DOI: 10.1016/j.rmed.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Positive expiratory pressure – Common clinical applications and physiological effects

Abstract: Breathing out against resistance, in order to achieve positive expiratory pressure (PEP), is applied by many patient groups. Pursed lips breathing and a variety of devices can be used to create the resistance giving the increased expiratory pressure. Effects on pulmonary outcomes have been discussed in several publications, but the expected underlying physiology of the effect is seldom discussed. The aim of this article is to describe the purpose, performance, clinical application and underlying physiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 88 publications
0
82
0
Order By: Relevance
“…The pressure produced and the breathing pattern, including expiratory force and expired volume, are important in achieving effective treatment. 15 Although known clinically, the significant differences between the resistors tested in this study had not been reported previously. It is hard to prove these differences in clinical settings because treatment depends on so many factors.…”
Section: Discussionmentioning
confidence: 65%
“…The pressure produced and the breathing pattern, including expiratory force and expired volume, are important in achieving effective treatment. 15 Although known clinically, the significant differences between the resistors tested in this study had not been reported previously. It is hard to prove these differences in clinical settings because treatment depends on so many factors.…”
Section: Discussionmentioning
confidence: 65%
“…18,19 To our knowledge, there are no published studies that evaluated OPEP therapy at increased intrapulmonary pressure, and there is a known risk with high pressures of complications, for example, pneumothorax. 20 The increased pressures generated through the incorrect use of OPEP devices, such as those seen in this study, therefore, are potentially detrimental.…”
Section: Discussionmentioning
confidence: 83%
“…Breathing exercises performed through nasal inspiration and slow and prolonged exhalation, such as the lip frenum, are expected to increase VT, promote pulmonary deflation and airway stability. 27,28 These effects, however, have not yet been fully elucidated in isolation or in association with wind toys.…”
Section: Discussionmentioning
confidence: 99%